The impact of the early phase of the COVID-19 pandemic on mental-health services in Europe. (9th August 2021) - Thome, Johannes; Deloyer, Jocelyn; Coogan, Andrew N.; Bailey-Rodriguez, Deborah; da Cruz e Silva, Odete A. B.; Faltraco, Frank; Grima, Cathleen; Gudjonsson, Snaebjorn Omar; Hanon, Cecile; Hollý, Martin; Joosten, Jo; Karlsson, Ingegerd; et al.
Abstract: Purpose: The current COVID-19 pandemic confronts psychiatric patients and mental health services with unique and severe challenges. Methods: In order to identify these trans-national challenges across Europe, an ad-hoc survey was conducted among 23 experts, each answering for one European or aligned country. Results: A number of important themes and issues were raised for the impact of COVID-19 on mental health and mental health services, barriers to service provision and future consequences. A number of key issues were reported by colleagues across several jurisdictions, even though these were at different stages of their national epidemics. Conclusions: Based on these findings, we articulate some important learnings from the early stages of the COVID-19 European pandemic, and highlight key considerations for all countries' mental health services as the current pandemic develops and for future pandemics.